Implementation of the Village Financial System Application (Siskeudes) in Efforts to Manage Village Finances in Ciangir Village, Legok District - Caroline Hemalian; Seno Santoso; Muhammad Ibrahim Rantau (Peneliti.net, 2023)
This research is entitled Application of the Village Financial System Application (Siskeudes) in Efforts to Manage Village Finances in Ciangir Village, Legok District. In organizing the village government, it is inseparable from financial factors, so that village financial management must be transparent and accountable. Therefore, the government developed the Village Financial System (Siskeudes) application. This application aims to make village financial management more orderly, clean, effective and efficient. This research was conducted in Ciangir Village, Legok District, Tangerang Regency. This study aims to determine the Application of the Village Financial System Application (Siskeudes) in Ciangir Village, Legok District. The type of research used in this research is descriptive research with a qualitative approach. Data collection techniques in this study used observation, interviews and documentation. The results showed that the application of the Village Financial System (Siskeudes) application in efforts to manage village finances in Ciangir Village is already running well. However, there are still inhibiting factors that need to be considered in terms of human resources. The Ciangir Village Government needs to improve the performance of its human resources so that village financial management can run optimally.